2021
DOI: 10.2174/1745017902117010136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alexithymia in Patients with Medically Unexplained Physical Symptoms: A Cross-sectional Study in Egypt

Abstract: Background: There is a high incidence of alexithymia in people who report medically unexplained symptoms. There have been limited studies on the prevalence of alexithymia in patients with medically unexplained physical symptoms (MUPS) in various ethnic and cultural backgrounds. Objective: This study aimed to estimate the prevalence of alexithymia in patients with MUPS and examine their socio-demographic data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…This finding might be attributed to higher alexithymia scores are frequently reported in older adults, which is consistent with the emotional changes related to aging as well as the majority of studied group aged between 20-40 years. The results of current study were matched with Rady et al (34) who studied that multiple comparisons between the six age groups demonstrated a developmental aspect of alexithymia and reveled that Total TAS-20 scores of teenagers and group of people who aged between 20-30 years were relatively higher than those aged between 40-50. As reported by Gundogmuş, Aydın and Algul (35) who found that high level of positive correlation between total TAS-20 scores and predictors of their study for instance age, gender, place of residence, monthly income, number of social media.…”
Section: Discussionsupporting
confidence: 87%
“…This finding might be attributed to higher alexithymia scores are frequently reported in older adults, which is consistent with the emotional changes related to aging as well as the majority of studied group aged between 20-40 years. The results of current study were matched with Rady et al (34) who studied that multiple comparisons between the six age groups demonstrated a developmental aspect of alexithymia and reveled that Total TAS-20 scores of teenagers and group of people who aged between 20-30 years were relatively higher than those aged between 40-50. As reported by Gundogmuş, Aydın and Algul (35) who found that high level of positive correlation between total TAS-20 scores and predictors of their study for instance age, gender, place of residence, monthly income, number of social media.…”
Section: Discussionsupporting
confidence: 87%
“…In clinical practice, many patients complain of physical symptoms that cannot be clearly explained even with appropriate medical examinations, and these patients are usually diagnosed as having medically unexplained symptoms (MUS) or functional somatic syndrome (FSS) [ 68 ]. These patients tended to show traits of alexithymia, including difficulty with identifying emotions, describing feelings to others, and externally oriented thinking [ 32 , 34 ]. Previous literature has shown that patients with alexithymia express their mental distress as relatively strong physical symptoms [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…If this heightened activity is not corrected, it may lead to exhaustion or the overwork of brain activity, eventually resulting in mental disorders [ 30 , 31 ]. Aging, alexithymia, alexisomia, and other predispositions make individuals vulnerable to mental overwork and further complications leading to diseases, including both mental and physical disorders [ 21 , 32 , 33 , 34 ]. In accordance with our hypothesis, previous studies suggested that people who have recurrent mental symptoms have typical characteristics of neuroticism, including a symptom referred to as “thinking too much” [ 29 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 As reported by the most recent contributions, 7 alexithymia is a cognitive deficit in emotional processing that could not allow to properly differentiate bodily sensations (thus signals of illness) from affects' arousal, with restricted imaginal activity. As one of the most relevant elements related to time to reperfusion treatment is the patient's decision to delay seeking care, it is intuitive that having strong alexithymia traits can determine indecision, difficulty in recognizing the severity of the symptoms 8 and therefore can be associated with the delay and with the probability of survival from the acute episode.…”
Section: Introductionmentioning
confidence: 99%